Brand Transformation in European Politics: The Rise and Limits of Nonclassical Names - Endre Borbáth; Swen Hutter (Perspectives on Politics, 2025)
Political parties in Europe are undergoing profound transformations, with many abandoning traditional brands. This study analyzes party names as indicators of ideological and organizational change, combining an original content analysis across 28 European countries (1945–2023) with two conjoint survey experiments. We find that “nonparty” names have become the majority, reflecting a shift away from ideology toward alternative forms of identification. While movement names appear in wavelike patterns linked to protest cycles, such as after the 2008 Great Recession, nonclassical names are especially prevalent among new, opposition, and right-wing parties. However, a paradox emerges: despite their growing adoption, nonclassical names do not easily yield the anticipated electoral benefits, as new parties seem to gain little from abandoning classical naming conventions. By tracing long-term naming trends and integrating survey-based experimental evidence, we advance debates on party transformation, political branding, and the evolving interplay between electoral and movement politics in contemporary democracies.
Keywords: 300; political parties; party brands; political crisis; conjoint experiments; Europe